Oldest known marine turtle? A new protostegid from the Lower Cretaceous of Colomb (2015)
Recent studies suggested that many fossil marine turtles might not be closely related to extant marine turtles (Chelonioidea). The uncertainty surrounding the origin and phylogenetic position of fossil marine turtles impacts our understanding of turtle evolution and complicates our attempts to develop and justify fossil calibrations for molecular divergence dating. Here we present the description and phylogenetic analysis of a new fossil marine turtle from the Lower Cretaceous (upper Barremian-lower Aptian, >120 Ma) of Colombia that has a minimum age that is >25 million years older than the minimum age of the previously recognized oldest chelonioid. This new fossil taxon, Desmatochelys padillai sp. nov., is represented by a nearly complete skeleton, four additional skulls with articulated lower jaws, and two partial shells. The description of this new taxon provides an excellent opportunity to explore unresolved questions about the antiquity and content of Chelonioidea. We present an updated global character-taxon matrix that includes D. padillai and marine turtles known from relatively complete specimens. Our analysis supports D. padillai as sister taxon of D. lowi within Protostegidae, and places protostegids as the sister to Pan-Dermochelys within Chelonioidea. However, this hypothesis is complicated by discrepancies in the stratigraphic appearance of lineages as well as necessarily complicated biogeographic scenarios, so we consider the phylogeny of fossil marine turtles to be unresolved and do not recommend using D. padillai as a fossil calibration for Chelonioidea. We also explore the definition of “marine turtle,” as applied to fossil taxa, in light of many littoral or partially marine-adapted fossil and extant lineages. We conclude that whereas the term “oldest marine turtle” depends very much on the concept of the term being applied, we can confidently say that D. padillai is the oldest, definitive, fully marine turtle known to date.